2017
DOI: 10.1038/s41598-017-02462-0
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Analysis of Glioma Growth in a Murine Model

Abstract: Five immunocompetent C57BL/6-cBrd/cBrd/Cr (albino C57BL/6) mice were injected with GL261-luc2 cells, a cell line sharing characteristics of human glioblastoma multiforme (GBM). The mice were imaged using magnetic resonance (MR) at five separate time points to characterize growth and development of the tumor. After 25 days, the final tumor volumes of the mice varied from 12 mm3 to 62 mm3, even though mice were inoculated from the same tumor cell line under carefully controlled conditions. We generated hypothese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…The model could be extended to include cancer stem cells to investigate the heterogeneous response of cancer cells to immunotherapies. Moreover, the in vivo data used to estimate the model parameters are indispensable to a more realistic model because the previous relevant works have showed that the slight changes in the model parameter might significantly influence the prediction results (47)(48)(49). In future work, we will develop data-driven A B D C Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…The model could be extended to include cancer stem cells to investigate the heterogeneous response of cancer cells to immunotherapies. Moreover, the in vivo data used to estimate the model parameters are indispensable to a more realistic model because the previous relevant works have showed that the slight changes in the model parameter might significantly influence the prediction results (47)(48)(49). In future work, we will develop data-driven A B D C Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we have investigated the applicability of a single-equation reaction-diffusion equation model (Rutter et al [24]) and a single-equation densitydependent diffusion model (Stepien et al [31]) to experimental data as well as analyzed the existence of traveling wave solutions in the latter paper. Stepien et al [31] and others such as Scribner and Fathallah-Shaykh [26] have shown that incorporating more complex dynamics into a single equation model can result in behavior characteristic of GBM invasion.…”
mentioning
confidence: 99%
“…Mathematically, we should quantify how much information is needed in order to recover the parameter distributions. Since we are, in effect, estimating many parameters to describe a joint distribution (instead of just 2 parameters for the constant-coefficient reaction-diffusion equation), it is imperative that we understand how much data is necessary to avoid the issue of parameter identifiability (which is a known issue in estimating parameters for the reaction-diffusion equation using only one type of imaging data [49]). Quantifying the uncertainty for the distributions estimated using the Prohorov metric framework remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%